Speech in action: degree of hand preference for grasping predicts speech articulation competence in children - Gonzalez, Claudia L. R.; Li, Fangfang; Mills, Kelly J.; Rosen, Nicole; Gibb, Robbin L. (Frontiers in Psychology, 2014)
In this report we provide compelling evidence for the relationship between right hand grasp-to-mouth (i.e. feeding) movements and language development. Specifically, we show that children (4-5 years old) who are more right-hand lateralized in picking up small food items for consumption show enhanced differentiation of the “s” and “sh” sounds. This result suggests that left hemisphere control of hand-to-mouth gestures may have provided an evolutionary platform for the development of language. The current investigation presents the exciting possibility that early right hand-to-mouth training could accelerate the development of articulation skills.